A délvidéki svábok I. világháborút megelőző radikalizálódásának kérdéséhez. : A német egyetemi hallgatók mozgalma - Orosz, László (Közép-Európai Közlemények, 2024)
The ethnic German movement in Hungary recognized early that a precondition of the battle against assimilation was the product of a determined youth intellectual stratum. The Vereinigung deutscher Hochschüler aus den Ländern der ungarischen Krone (Association of German Students from the Lands of the Hungarian Crown) was established at the University of Vienna, the main gravitational point of selfassertive German youths from Hungary, in 1899. The endeavors of the organization in support of the German body politic engendered a fierce national reaction in Hungary. In addition to press battles in public and on the surface, the association carried out wholly effective background and small-scale tasks hidden from the view of observers, especially in the German settlement blocks of Bácska, Bánát and Szerémség, which provided many members. This in itself afforded every segment of enlightenment and propaganda in terms of awakening national consciousness, as well as the cultural upkeep of German villages through books and public libraries, the organization of commemorations and celebrations of German individuals who instilled national pride, the issuance and dissemination of flyers and even the effectuation of legal aid and covert signature collection drives. These youths went on to make up the political leadership of the German communities in the successor states after 1918.